1974
DOI: 10.1002/recl.19740930302
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the antioxidant action of dialkyl sulfoxides II. Aspects of the antioxidant and pro‐oxidant actions of sulfoxides

Abstract: Abstract. This paper analyses several complicating factors which can play a role in the inhibition of autoxidation by dialkyl awlfoxides. the uncomplicated case having been dealt with in the first paper'. It was found that in those cases where the autoxidation proceeds via tertiary peroxy radicals. sulfoxides yielding tertiary (or, possibly, also secondary) alkylsulfenic acids show poor antioxidant activity. This is attributed to the generation of radicals from the sulfinic acid perester formed by the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In 1974, Koelewijn and Berger16 provided evidence that organosulfur compounds can act as RTAs. They showed that di- tert -butylsulfide, upon oxidation to the corresponding sulfoxide, is a good RTA.…”
Section: Introductionmentioning
confidence: 99%
“…In 1974, Koelewijn and Berger16 provided evidence that organosulfur compounds can act as RTAs. They showed that di- tert -butylsulfide, upon oxidation to the corresponding sulfoxide, is a good RTA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these stabilizing sacrificial functions can be chosen to give new sulfonic acid groups once oxidized (thiols, disulfides, etc. ), therefore increasing the concentration of acid groups in the membrane and improving its proton conductivity. These hybrid membranes should then exhibit excellent chemical and thermomechanical stability, excellent water retention, and therefore excellent proton conduction at low relative humidity.…”
Section: Introductionmentioning
confidence: 99%